Mapping discrimination against Black Americans in Kim Johnson's This is My America - Gabrielle Mercedez Ferry; Christy Tisnawijaya (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Racial discrimination is still a conspicuous issue in literature, as in Kim Johnson's This is My America (2020). This study aims to scrutinize the racism issues in the novel. The Beaumont family experiences racial prejudice: Mr. Beaumont, the father, is incarcerated due to the accusation of killing a white couple; Tracy, the daughter, is assaulted at school due to the father's prosecution; and Jamal, the son, is convicted of killing a white girl due to the father's history. This study employs a close reading methodology (Ohrvik, 2024) to gain a comprehensive interpretation of the narrative. Moreover, this study utilizes Alport's prejudice scheme (1954) and Pincus' discrimination frame (2000) to discuss the story's conflict in-depth. The discussion shows that This is My America portrays three types of discrimination: individual, institutional, and structural. The discriminatory acts in the forms of unjust laws, social exclusion, and physical attacks are enforced by the belief in white supremacy.